Transport of UDP-rhamnose by URGT2, URGT4, and URGT6 modulates rhamnogalacturonan-I length. Issue 3 (29th December 2020) - Saez-Aguayo, Susana; Parra-Rojas, Juan Pablo; Sepúlveda-Orellana, Pablo; Celiz-Balboa, Jonathan; Arenas-Morales, Verónica; Sallé, Christine; Salinas-Grenet, Hernán; Largo-Gosens, Asier; North, Helen M; Ralet, Marie-Christine; Orellana, Ariel
Abstract: Rhamnogalacturonan-I biosynthesis occurs in the lumen of the Golgi apparatus, a compartment where UDP-Rhamnose and UDP-Galacturonic Acid are the main substrates for synthesis of the backbone polymer of pectin. Recent studies showed that UDP-Rha is transported from the cytosol into the Golgi apparatus by a family of six UDP-rhamnose/UDP-galactose transporters (URGT1-6). In this study, analysis of adherent and soluble mucilage (SM) of Arabidopsis thaliana seeds revealed distinct roles of URGT2, URGT4, and URGT6 in mucilage biosynthesis. Characterization of SM polymer size showed shorter chains in the urgt2 urgt4 and urgt2 urgt4 urgt6 mutants, suggesting that URGT2 and URGT4 are mainly involved in Rhamnogalacturonan-I (RG-I) elongation. Meanwhile, mutants in urgt6 exhibited changes only in adherent mucilage (AM). Surprisingly, the estimated number of RG-I polymer chains present in urgt2 urgt4 and urgt2 urgt4 urgt6 mutants was higher than in wild-type. Interestingly, the increased number of shorter RG-I chains was accompanied by an increased amount of xylan. In the urgt mutants, expression analysis of other genes involved in mucilage biosynthesis showed some compensation. Studies of mutants of transcription factors regulating mucilage formation indicated that URGT2, URGT4, and URGT6 are likely part of a gene network controlled by these regulators and involved in RG-I synthesis. These results suggest that URGT2, URGT4, and URGT6 play different roles in the biosynthesis of mucilage, and the lack of all three affects the production of shorter RG-I polymers and longer xylan domains. Abstract : Three UDP-rhamnose/UDP-galactose transporters play different roles in the biosynthesis of mucilage and the lack of all three results in the production of shorter rhamnogalacturonan polymers and altered xylan domains.